Biomaterials reinforced MSCs transplantation for spinal cord injury repair - Teng Ma; Jiahe Wu; Jiafu Mu; Jianqing Gao (Elsevier, 2022)
Due to the complex pathophysiological mechanism, spinal cord injury (SCI) has become one of the most intractable central nervous system (CNS) diseases to therapy. Stem cell transplantation, mesenchymal stem cells (MSCs) particularly, appeals to more and more attention along with the encouraging therapeutic results for the functional regeneration of SCI. However, traditional cell transplantation strategies have some limitations, including the unsatisfying survival rate of MSCs and their random diffusion from the injection site to ambient tissues. The application of biomaterials in tissue engineering provides a new horizon. Biomaterials can not only confine MSCs in the injured lesions with higher cell viability, but also promote their therapeutic efficacy. This review summarizes the strategies and advantages of biomaterials reinforced MSCs transplantation to treat SCI in recent years, which are clarified in the light of various therapeutic effects in pathophysiological aspects of SCI.